2021
DOI: 10.1111/ajad.13211
|View full text |Cite
|
Sign up to set email alerts
|

Substance use, depression, and loneliness among American veterans during the COVID‐19 pandemic

Abstract: Background and ObjectivesBehavioral health issues, such as substance use, depression, and social isolation, are of grave concern during COVID‐19, especially for vulnerable populations. One such population is US veterans, who have high rates of pre‐existing behavioral health conditions and may thus be at‐risk for poorer outcomes. The current study aimed to investigate substance use among US veterans during COVID‐19 as a function of pre‐existing depression, loneliness, and social support.MethodsWe investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
1
18
0
3
Order By: Relevance
“…In Peter's study, there was no significant difference in alcohol use before and after the global outbreak in the group from the National Health and Resilience in Veterans Study, which was conducted in the USA from November 18, 2019, to December 19, 2020( Na et al, 2021a ). However, decreased alcohol use in another group of veterans from the USA was observed in other previous studies( Davis et al, 2021 ; Fitzke et al, 2021 ), which was consistent with a study in UK( Sharp et al, 2021 ). In addition, several studies showed that the prevalence of anxiety has increased during the pandemic, while Iverson et al found no difference in anxiety symptoms from the pre-pandemic to peri-pandemic periods( Iverson et al, 2022 ).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Peter's study, there was no significant difference in alcohol use before and after the global outbreak in the group from the National Health and Resilience in Veterans Study, which was conducted in the USA from November 18, 2019, to December 19, 2020( Na et al, 2021a ). However, decreased alcohol use in another group of veterans from the USA was observed in other previous studies( Davis et al, 2021 ; Fitzke et al, 2021 ), which was consistent with a study in UK( Sharp et al, 2021 ). In addition, several studies showed that the prevalence of anxiety has increased during the pandemic, while Iverson et al found no difference in anxiety symptoms from the pre-pandemic to peri-pandemic periods( Iverson et al, 2022 ).…”
Section: Introductionsupporting
confidence: 91%
“…Nonetheless, the impact of COVID-19 on alcohol use in veterans was inconsistent across studies. Compared with pre-pandemic, Dominic et al reported that 30% of veterans increased alcohol use during the pandemic( Murphy et al, 2022b ), while three studies showed a reduced rate of alcohol use among veterans( Davis et al, 2021 ; Fitzke et al, 2021 ; Sharp et al, 2021 ). In Peter's study, however, there was no significant difference in alcohol use before and during the global outbreak( Na et al, 2021a ).…”
Section: Resultsmentioning
confidence: 99%
“…Loneliness and boredom, stress, reactive anxiety and depression as well as social distancing were identified as driving factors for cannabis use, as well as for intake of alcohol, tobacco and other drugs in adolescents and adult populations during the pandemic (e.g., Fitzke et al 2021;Somé et al 2022;Reilly et al 2022;Gutkind et al 2022). In adolescents, cannabis use was related to larger functional impairment in daily activities and this relation was mediated by the sequential effects of difficulty with emotion regulation and pandemic-related distress.…”
Section: Cannabis Use and Mental Healthmentioning
confidence: 97%
“…Veterans were at-risk for social isolation and loneliness before the pandemic. Unfortunately, veterans are now increasingly isolated due to attempts to mitigate community spread of COVID-19 (Fitzke et al, 2021;. There are risk factors associated with being socially isolated such as anxiety depression, sleep problems, suicidal ideation, post-traumatic stress symptoms, and an increased risk for and other mental and physical limitations.…”
Section: Rationale Informing the Projectmentioning
confidence: 99%